Beyond medical pluralism: characterising health-care delivery of biomedicine and traditional medicine in rural Guatemala. Issue 4 (3rd April 2018) - Hoyler, Elizabeth; Martinez, Roxana; Mehta, Kurren; Nisonoff, Hunter; Boyd, David
ABSTRACT: Although approximately one half of Guatemalans are indigenous, the Guatemalan Maya account for 72% of the extremely poor within the country. While some biomedical services are available in these communities, many Maya utilise traditional medicine as a significant, if not primary, source of health care. While existing medical anthropological research characterises these modes of medicine as medically dichotomous or pluralistic, our research in a Maya community of the Western Highlands, Concepción Huista, builds on previous studies and finds instead a syncretistic, imbricated local health system. We find significant overlap and interpenetration of the biomedical and traditional medical models that are described best as a framework where practitioners in both settings employ elements of the other in order to best meet community needs. By focusing on the practitioner's perspective, we demonstrate that in addition to patients' willingness to seek care across health systems, practitioners converse across seemingly distinct systems via incorporation of certain elements of the 'other'. Interventions to date have not accounted for this imbrication. Guatemalan governmental policies to support local healers have led to little practical change in the health-care landscape of the country. Therefore, understanding this complex imbrication is crucial for interventions and policy changes.